Developing An Atlas Based on Biodiversity of Plants and Animals in Wetland - Muhsinah Annisa; Fadlan Muchlas Abrori; Teguh Prasetio; Herti Prastitasari; Asrani Asrani (Yayasan Keluarga Guru Mandiri, 2022)
This study aims to develop an atlas based on the wetland biodiversity of South Kalimantan. The development of the atlas in this research uses a 4-D development model, which consists of define, design, develop, and disseminate. However, the development stage only reaches the development stage. The instrument in this study consisted is Instruments at the research phase include species identification sheet, ecosystem identification sheet, and community interview sheet, and the other Instruments at the development phase include learning atlas validation sheets. The results of documentation and identification showed that there were 83 species of plants, animals, and plants, with details of 65% plant species and 35% animal species. Furthermore, related to the development of a learning atlas based on the assessment of content experts, media experts, and practitioners, scores above 90% were obtained and obtained valid criteria. Meanwhile, the assessment of linguists gets an assessment of 80 - 88% with quite valid criteria.Â The media atlas developed for further research can be applied to classroom learning to determine its effect on learning outcomes. Another thing that can be done is to change the atlas format in digital form so that it can be used virtually during the COVID-19 pandemic.